Molecular toolkit for inbred line screening and purification of Maize (Zea mays) - Heredia, Maria Cristina C.; Austria, Rovel Emman G.; Ocampo, Eureka Teresa M. (2018)
Inbred lines are produced by self-pollinating maize plants for several cycles resulting in populations that are morphologically similar and genetically stable, and pure. Inbred lines are valuable parental materials in the development of hybrid varieties. Hence, genetic purity of inbred lines should be maintained so that hybrids produced are always of the same quality and genetic make-up. However, purification of inbreds by conventional methods can be difficult since morphological features can be similar in plants that are highly diverse. An alternative is to use molecular markers to screen, identify, and verify the genetic similarity of inbred lines. In this study, simple sequence repeats (SSRs) were used to identify genetically similar plants. One hundred and ten SSR markers representing the ten chromosomes of maize were selected from published literature and databases. The published primers of these markers were used to amplify the marker regions from isolated DNA of five maize inbreds (Sukmaraga 9, Sukmaraga 16, Lamuro 8, CW80116) and five native varieties (Pastilan, Banlon, TinuguibB, CalimpusA, KabagtikA). The amplified DNA bands were scored for polymorphism. Thirty-two polymorphic markers (representing at least two for every chromosome) were selected and utilized for preliminary inbred line screening. The first and second batch of screening among known Philippine inbreds showed that the yellow maize inbreds Pi17 and Pi23 gave acceptable homozygosity of â?¥90%, while white maize inbred lines P9 and P29 were highly heterozygous. Selected plants were selfed and advanced into the succeeding generation. True inbred lines were distinguished among the conventionally characterized Philippine â??inbredâ?? lines with the assistance of SSR markers.